PERENCANAAN DAN INVESTASI KEUANGAN UNTUK PENDIDIKAN ANAK PADA IBU-IBU KELURAHAN SEMOLOWARU SURABAYA - Tuty Lindawati; P. Julius F. Nagel; Ninuk Muljani; Fransisca Natalia (LPPM, Universitas Katolik Widya Mandala Surabaya, 2022)
This community service was carried out because there was a problem with the women of Semolowaru Village, Surabaya regarding children's education funds that they had never prepared, because they did not understand how to plan finances and choose investments for their children's education funds, so they experienced difficulties when the education funds were needed. This community service aims to develop knowledge, skills, add insight, and ability of the women of Semolowaru Village, Surabaya on the importance of planning and financial investment for children's education. The service method applied is in the form of lectures, discussions, and exercises to plan and choose appropriate financial investments for children's education. The target of this activity is the women of Semolowaru Village, Surabaya, totaling 25 people. The implication of the results of this community service is that the women of Semolowaru Village, Surabaya are able to make financial plans for their children's education and are able to choose appropriate financial investments for their children's education.